β-Cyclodextrin metal-organic framework as a green carrier to improve the dissolution, bioavailability, and liver protective effect of luteolin - Dan Yang; Min Zhao; Yihe Huang; Liwen Chen; Jiqin Fang; Jiaonan Liu; Miao Wang; Chunjie Zhao (Elsevier, 2024)
The incidence of acetaminophen-induced liver injury has increased, but effective prevention methods are limited. Although luteolin has hepatoprotective activity, its low solubility and bioavailability limit its applications. Cyclodextrin metal-organic frameworks (CD-MOFs) possess 3D-network structures and large inner cavities, which make them excellent carriers of poorly soluble drugs. In this study, we used CD-MOFs as carriers to improve the dissolution of luteolin and assessed their antioxidant activity, bioavailability, and hepatoprotective effects. Luteolin was loaded into β-CD-MOF, γ-CD-MOF, β-CD, and γ-CD, and characterized by powder X-ray diffractometry (PXRD) and thermogravimetric analysis (TGA). Our results showed that luteolin-β-CD-MOF was the most stable. The main driving forces were hydrogen bonds and van der Waals forces, as determined by molecular simulation. The loading capacity of luteolin-β-CD-MOF was 14.67 wt%. Compared to raw luteolin, luteolin-β-CD-MOF exhibited a 4.50-fold increase in dissolution and increased antioxidant activity in vitro. Luteolin-β-CD-MOF increased the bioavailability of luteolin by approximately 4.04- and 11.07-fold in healthy rats and liver injured rats induced by acetaminophen in vivo, respectively. As determined by biochemical analysis, luteolin-β-CD-MOF exhibited a better hepatoprotective effect than raw luteolin in rats with acetaminophen-induced liver injury. This study provides a new approach for preventing acetaminophen-mediated liver damage.